Comparison of the Adsorption Ability of MgAl-HC, CaAl-HC, and ZaAl-HC Composite Materials Based on Duku Peel Hydrochar in Adsorption of Direct Green Anionic Dyes - Novie Juleanti; Normah Normah; Patimah Mega Syah Bahar Nur Siregar; Alfan Wijaya; Neza Rahayu Palapa; Tamizi Taher; Nurlisa Hidayati; Risfidian Mohadi; Aldes Lesbani (Indonesian Journal of Chemistry, 2022)
Preparation of composite material from layered double hydroxide (LDH) with hydrochar (HC) from duku peel produces CaAl-HC, MgAl-HC, and ZnAl-HC have shown the success of the preparation process as evidenced by characterizations such as XRD and FT-IR. The XRD characterization data evidenced the typical diffraction of the hydrochar around 2θ = 20° in the composite material. FTIR analysis is a characterization that supports the success of composite materials, which showed the presence of typical vibrations of HC at 3245, 2931, and 1635 cm–1 contained in the composite spectrum. The application of MgAl-HC, CaAl-HC, and ZnAl-HC composites as adsorbents showed Qmax (adsorption ability) values of 94.340 mg/g, 128.205 mg/g, and 89.286 mg/g. Overall the adsorption process is endothermic with a positive enthalpy value, and a negative Gibbs free energy value indicates a spontaneous adsorption process. The isotherm model of MgAl-HC, CaAl-HC, and ZnAl-HC show that the Langmuir isotherm model is more dominant, as indicated by the R2 value closer to 1 which indicates that the adsorption process takes place in a monolayer.